its like the pythagorean theory (sort of)
you have one part of the equation and the answer
j+4 3/8 plus what gives you 8?
its 3 5/8
do it like this
j=8-4 3/8
you just substitute for j
2006-11-28 12:45:23
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
j + 4 3 / 8 = 8
- 4 3 / 8 -4 3 / 8
j = 3 5 / 8
2006-11-28 20:51:54
·
answer #2
·
answered by anonymous 3
·
0⤊
0⤋
You start with:
j + 4 3/8 = 8
To solve this problem you must move terms around to leave the variable "j" on one side by itself. Right now it has + 4 3/8 on the same side as the "j".
To move the + 4 3/8 you must do just the opposite to both sides of the equation. The opposite of "+ 4 38" is "- 4 3/8". Do this to both sides:
j + 4 3/8 - 4 3/8 = 8 - 4 3/8
+ 4 3/8 - 4 3/8 = 0 on the left side. Now you have:
j = 8 - 4 3/8
8 - 4 3/8 = 3 5/8 so j = 3 5/8
2006-11-28 20:50:49
·
answer #3
·
answered by physandchemteach 7
·
0⤊
1⤋
The first thing I would do is substract 4 3/8 from each side:
j + 4 3/8 - 4 3/8 = 8 - 4 3/8
j = 8 - 4 3/8
then I would convert the 8 to 64/8 and convert 4 3/8 to 35/8
j = 64/8 - 35/8
j = 29/8 change to mixed number
j = 3 5/8
2006-11-28 20:50:25
·
answer #4
·
answered by Tom B 1
·
0⤊
1⤋
j + 4 3/8 = 8
so you have "something" + 4 3/8 = 8
so you take away the 4 3/8 from the 8 and that will leave the answer
when dealing with 8ths 8/8 = 1
8 becomes 7 8/8 minus the 4 3/8
so 7 minus 4 = 3
and 8/8 minus 3/8 = 5/8
so then j = 3 5/8
to check you add 3 5/8 to 4 3/8 and get 7 and 8/8
8/8 = 1
so add 7 to 1 = 8
2006-11-28 20:51:51
·
answer #5
·
answered by Anonymous
·
0⤊
1⤋
That's a pretty easy one. 4+3 = 7, you got that part, I'm sure
3/8 + 5/8 = 8/8 or 1
7+1=8
So 3 5/8 + 4 3/8 = 8
2006-11-28 20:45:53
·
answer #6
·
answered by glitterkittyy 7
·
1⤊
2⤋
subtract 4 3/8 from 8
2006-11-28 20:45:37
·
answer #7
·
answered by Bestie 6
·
0⤊
1⤋
4 3/8 is really 35/8 right? right!
okay sooo...
8 is also know as 64/8
so you have
j = 64/8 - 35/8 = 29/8 which is the same as saying 3 5/8
10 points please
2006-11-28 20:48:42
·
answer #8
·
answered by DW 2
·
0⤊
1⤋